Efektivitas Penerapan Aplikasi Sistem Informasi Kesejahteraan Sosial - Next Generation (SIKS-NG) Dalam Pengusulan Bantuan Sosial - Mursyidah, Lailul; Arydianti, Fadila Putri (Kolaborasi : Jurnal Administrasi Publik, 2024)
This research aims to find out, analyze, and describe the effectiveness of the application of the Social Welfare Information System - Next Generation (SIKS-NG) application in proposing social assistance. This research uses a qualitative descriptive method with data collection techniques through direct observation, interviews, and documentation. The informants in this study were determined by purposive sampling, namely the Keper Village SIKS-NG operator, Mr. Imam Sugiantoro as the Head of the Welfare Section. The results of the research adjusted to the theory of Richard M. Steers show that in the adaptation indicator there are still obstacles in the lack of training, system update problems, and technical constraints. In the goal achievement indicator, there is a mismatch between the data on beneficiaries proposed by the village and those that come down from the center. And the integration indicator shows that there is a lack of socialization related to this application so that community involvement in proposing beneficiaries is also lacking.